2015
DOI: 10.1002/cncr.29417
|View full text |Cite
|
Sign up to set email alerts
|

Male‐female patient differences in the association between end‐of‐life discussions and receipt of intensive care near death

Abstract: Background Patient gender plays a significant role in patient-physician communication, patient illness understanding and aggressiveness of end of life (EoL) care. However, little is known about the extent to which gender differences in the effects of EoL discussions on EoL care contribute to gender differences in EoL care. The present study aims to determine if gender differences exist in receipt of intensive care unit (ICU) care near death and in the association between EoL discussions and receipt of ICU EoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 37 publications
13
78
1
4
Order By: Relevance
“…In our study, men were found to be more exposed to chemotherapy at the end of life than women. This sex bias has been described before, both in end-of-life care settings 44 and in other settings. 45,46 These findings raise considerable concern for the quality of cancer care near the end of life, as increasing evidence suggests that continuation of chemotherapy close to death is most likely indicative of overuse.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, men were found to be more exposed to chemotherapy at the end of life than women. This sex bias has been described before, both in end-of-life care settings 44 and in other settings. 45,46 These findings raise considerable concern for the quality of cancer care near the end of life, as increasing evidence suggests that continuation of chemotherapy close to death is most likely indicative of overuse.…”
Section: Discussionsupporting
confidence: 68%
“…Variations in quality markers of end-of-life care have been observed across physicians [8,9], health centers [10], geographical regions [1114], and various subgroups of the population [9,1518]. In particular, racial/ethnic disparities both in receipt of aggressive care and hospice use have been documented extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Given that EoL outcomes are strongly influenced by culture, including religious and racial/ethnic disparities in treatment preferences, planning, and care, research is needed to determine the generalizability of these findings across more diverse settings. That said, prior research has indicated that prognostic understanding is critical to improving EoL care planning across a variety of races, genders, and patient groups . Second, the present analyses are cross sectional.…”
Section: Discussionmentioning
confidence: 99%
“…That said, prior research has indicated that prognostic understanding is critical to improving EoL care planning across a variety of races, genders, and patient groups. 23,25,26 Second, the present analyses are cross sectional. Causal relationships between patient and caregiver prognostic understanding and completion of DNR orders cannot be inferred.…”
Section: Study Limitationsmentioning
confidence: 99%